Hepatocellular Carcinoma: Risk Factors and Diagnosis - Ghina Syafinatunnajah; Ananda Rizkia; Donna Diva Widyantari; Ni Pt Wr Pradnya Nirmala Putri; Catarina Budyono (Jurnal Biologi Tropis, 2023)
Hepatocellular carcinoma, also known as hepatocarcinoma, is the most frequent type of primary liver cancer and the world's second leading cause of death, with a mortality rate of 700.000 per year. Due to the difficulty in diagnosing hepatocarcinoma because there are no obvious symptoms, the survival rate of hepatocarcinoma patients is still very low, particularly in Southeast Asian countries. Hepatocarcinoma is still a major health issue in Indonesia, with a very low median survival rate. The number of risk factors that cause hepatocarcinoma is what causes differences in hepatocarcinoma incidence across countries. This literature review aims to determine risk factors and to confirm the diagnosis of hepatocarcinoma. This literature review was conducted using the keywords “Hepatocellular Carcinoma AND risk factors AND diagnosis” from PubMed, Google Scholar, and non-peer-reviewed literature. This article uses 16 articles that were used as references in its preparation. In conclusion, hepatitis B and C virus, liver cirrhosis, fatty liver disease, diabetes, alcohol use, aflatoxin exposure, aristolochic acid exposure, smoking, and HIV are risk factors for hepatocarcinoma. On all individuals with hepatocarcinoma risk factors, screening procedures with US and AFP were carried out. An abdominal CT scan or an MRI with contrast can both be used to provide a firm diagnosis of hepatocarcinoma. A liver biopsy is used to confirm the diagnosis of space-occupying lesions that lack typical imaging characteristics.